Composition Dependence on the Evolution of Nanoeutectic in CoCrFeNiNbx (0.45 ≤ x ≤ 0.65) High Entropy Alloys. Issue 4 (13th December 2017) - Chanda, Barnasree; Das, Jayanta
Abstract : The effect of Nb addition in arc‐melted CoCrFeNiNb x (0.45 ≤ x ≤ 0.65) high entropy alloys (HEAs) on the phase evolution, stability, refinement of the microstructure, and mechanical properties are investigated. Minor fluctuation of Nb modifies the microstructure from hypoeutectic ( x = 0.45) to eutectic ( x = 0.5) and hypereutectic ( x = 0.55) containing 134–200 nm thin nano‐lamellar FCC γ ‐Ni and HCP Fe2 Nb‐type Laves phases. The nano‐eutectic CoCrFeNiNb0.5 HEA shows high yield strength (2060 ± 5 MPa) and strain hardening up to 2200 ± 10 MPa with 17.0 ± 0.5% compressive plasticity. Transmission electron microscopic studies of partially deformed specimen has been revealed that the activity of dislocations is present in the eutectic FCC/Laves lamellae and at their interface. The stability of the phases in CoCrFeNiNbx and other eutectic HEAs as reported in the literature, has been assessed by estimating mixing entropy (Δ Smix ), mixing enthalpy (Δ Hmix ), atomic size differences ( δ ), valence electron concentration, Pauling electronegativity (Δ χP ), and Allen electronegativity (Δ χA ) to predict the evolution and coexistence of eutectic phases. Abstract : The microstructure of CoCrFeNiNb x (0.45 ≤ x ≤ 0.65) high entropy alloys contain proeutectic dendrites along with nanolamellar γ ‐Ni and Laves phases, which show high yield strength of 2060 MPa and large plasticity of 17% due to the movement of dislocations. The stability of the phases has been assessed using thermodynamic parameter, atomic size parameter, valance electron concentration, and electronegativity parameters.